Biomassa e nutrientes em um povoamento de Eucalyptus urograndis estabelecido em solo sujeito a arenização no sul do Brasil - Carvalho, Renata Reis de (2014)
The study on nutrient cycling in plantation of eucalyptus provides alternative recovery and management avoiding having reduction in future productivity of plantations, contributing to sustainable management. The current study was conducted in the municipality of Alegrete, Rio Grande do Sul, Brazil, in an area belonging to the enterprise Stora Enso S/A. The objective was to assess biomass and nutrient dynamics in a stand of Eucalyptus urograndis in soil subjected to sand effects in southern Brazil. From an inventory, 12 trees were selected and sampled for the quantification of aboveground biomass. The root system was sampled through the excavation of four trees. For the sampling of the leaf litter produced, 16 collectors of 0,5 m² of useful area were installed for the evaluation of leaves, miscellany and thin branches (diameter less than or equal to 5 mm). In addition, sub-plots were installed for the collection of thick branches (diameter greater than 5 mm). The estimated total biomass was of 75 Mg ha-1, with the following distribution 5,5%; 10,2%; 7,7%; 61,2% and 15,4% in the leaves, branches, stem bark, stem wood and roots, respectively. The litterfall in the year was 8,1 Mg ha-1, having its peak between the months of November and December. The litter accumulation was 9,7 Mg ha-1. The amount of nutrients in biomass had the following magnitude of the macronutrients: Ca > K > N > Mg > S > P. The amount of biomass was micronutrients: Mn> Fe> B> Zn> Cu. The litterfall followed the order of the following fractions: leaves > thin branches > thick branches > miscellany. The Ca concentration was greater in thick branches and N was higher in the leaves. The lowest P concentration was observed in the thick branches. Regarding the micronutrients, values showed variations and presented the following order: Mn > Fe > B > Zn > Cu. The species showed good efficiency in using nutrients. Based on nutrient removal in different scenarios harvest of biomass, nutritional balance and potential number of rotations of the wood harvesting + stem bark of removes over 50% of all accumulated in above-ground biomass nutrients. Performing their harvest of commercial timber leaving residues on the soil itself contributes to nutrient cycling avoiding decreased productivity in the next rotation.